Assessment of radiation damage of the first wall of a fusion neutron source DEMO-FNS with a blanket for the transmutation of minor actinides. (16th November 2021) - Zhirkin, A.V.; Budaev, V.P.; Goltsev, A.O.; Dedov, A.V.; Komov, A.T.; Kuteev, B.V.; Lanye, I.V.
Abstract: The design of the demonstration fusion neutron source (DEMO-FNS) demonstration fusion–fission hybrid facility is carried out at the National Research Center 'Kurchatov Institute' in Russia. For the implementation of the DEMO-FNS project, it is important to assess the effect of the fast neutron spectrum on radiation-induced damage to the device materials, primarily the materials of the first wall, which is the most problematic unit of the device. Due to the lack of real hybrid fusion devices, the study can only be carried out using computer simulations of the experiment. A computer simulation using the Monte Carlo method was carried out to calculate the developed three-dimensional full-scale model of the DEMO-FNS reactor with a blanket for the transmutation of minor actinides. The MCNP-4 code was used with cross-sections from the FENDL-2.1 and ENDF/B-6 files, as well as with cross sections for calculating radiation displacements. The neutron spectrum in the first wall of DEMO-FNS was determined at the power of a volumetric deuterium–tritium neutron of 1.42 × 10 19 n s −1 . It was found that beryllium as a plasma-facing material has too short lifetime under the neutron load on the first wall and divertor plates of DEMO-FNS. The replacement beryllium to tungsten is problematic and requires special study. Copper alloys have sufficient resistance to the effects of neutron radiation of DEMO-FNS for one full power year, but will require several replacements when operating the device for more than 10 years. The steels used in fast reactors can meet the operational requirements of the first wall of DEMO-FNS. To solve the problem of choosing materials for the first wall of DEMO-FNS, new experimental researches on changes in the physical properties of these materials in the fast neutron spectrum are needed.